Permeability and material characteristics of vulcanized latex film during and following cyclic fatigue in a saline environment - Dillon J G; Schroeder L W (Journal of Applied Polymer Science, 1997)
The importance of stress or fatigue as a source of latex glove failure has been mentioned in several recent studies, but little work has been done to examine the underlying mechanism of these failures. This work was undertaken to develop techniques for very early detection of structural changes in glove barriers. This was done by monitoring the ion permeability and electrical properties of vulcanized latex glove material during cyclic fatigue in saline. Alteration in the conductance and capacitance of the membrane during the fatigue cycle showed that catastropic failure of the material was preceded by deviation in the conductance of the membrane 8-10min before rupture of the material. Disruption of the material coincided with capacitive discharge of and ion transport across the membrance. Follow-up examination by optical (100x) and scanning electron microscopy (SEM) revealed failure of the original fibril network structure surrounding the latex particles. Failure corresponded to processes consistent with repeated stress and rupture of the fibrils responsible for maintaining membrane integrity. Cyclic creep-strain measurements were carried out on the latex gloev material. The estimated strain during cyclic fatigue was consistant with use during normal flexing of the glove finger. The fatigue life-time of the glove material was found to be about 2h. Based on these studies, we conclude that failure of the glove material due to hole formation is preceded by gradual thinning (and weakening) of the membrane in localized regions. This suggests that latex inhomogeneities (defects) are the ultimate cause of failure. These findings confirm the importance of stress in explaining the source of some glove material filures, especially those failures not obviously accompanied by sharp instrument or needle penetrations. The results of the fatigue study emphasize the importance of changing gloves during prolonged use.
Source Year: 1997
Keywords: Vulcanized latex film